THE USE OF PHOTOACOUSTIC - SPECTROSCOPY TO DETERMINE THE CRITICAL DISTANCE FOR ELECTRON-TRANSFER - Cornelio, M. L.; Sanches, R. (Elsevier B.V., 1994)
Photoacoustic spectroscopy was used to determine the critical distance for electron transfer from porphyrin to quinone molecules randomly dispersed in a polymeric matrix. An enhancement of the porphyrin signal was observed as the quinone concentration was increased. The data was analyzed according to the Perrin model [1] and it was found that the electron transfer occurred if the prophyrin-quinone distance was less than 33 Angstrom. To confirm the validity of the method, the fluorescence quenching was also measured for the samples. In this case, the same critical distance was obtained.
Keywords: PHOTOACOUSTIC; FLUORESCENCE; ELECTRON TRANSFER; PERRIN MODEL